ChemInform Abstract: Electromagnetic Susceptibility Anisotropy and Its Importance for Paramagnetic NMR and Optical Spectroscopy in Lanthanide Coordination Chemistry. Issue 24 (27th May 2016) - Blackburn, Octavia A.; Edkins, Robert M.; Faulkner, Stephen; Kenwright, Alan M.; Parker, David; Rogers, Nicola J.; Shuvaev, Sergey
Abstract: Review: 103 refs.